2009
DOI: 10.1088/0031-9155/54/9/002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the spatial and temporal accuracy of heating in the prostate gland using transurethral ultrasound therapy and active MR temperature feedback

Abstract: A new MRI-guided therapy is being developed as a minimally invasive treatment for localized prostate cancer utilizing high-intensity ultrasound energy to generate a precise region of thermal coagulation within the prostate gland. The purpose of this study was to evaluate in vivo the capability to produce a spatial heating pattern in the prostate that accurately matched the shape of a target region using transurethral ultrasound heating and active MR temperature feedback. Experiments were performed in a canine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 44 publications
3
66
0
1
Order By: Relevance
“…MR THERMOMETRY IS increasingly used to guide and monitor thermotherapy procedures for cancer treatment. These procedures include focused ultrasound (FUS) ablation (1)(2)(3)(4), radiofrequency (RF) ablation (5), laser ablation (6,7), and mild adjuvant RF hyperthermia (RF-HT) (8)(9)(10). These relatively noninvasive procedures require accurate and fast estimates of temperature and thermal dose over a region to ensure maximal damage to the diseased tissue, while sparing surrounding healthy tissue from inadvertent damage.…”
Section: Conclusion: Ex Vivo and In Vivo Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MR THERMOMETRY IS increasingly used to guide and monitor thermotherapy procedures for cancer treatment. These procedures include focused ultrasound (FUS) ablation (1)(2)(3)(4), radiofrequency (RF) ablation (5), laser ablation (6,7), and mild adjuvant RF hyperthermia (RF-HT) (8)(9)(10). These relatively noninvasive procedures require accurate and fast estimates of temperature and thermal dose over a region to ensure maximal damage to the diseased tissue, while sparing surrounding healthy tissue from inadvertent damage.…”
Section: Conclusion: Ex Vivo and In Vivo Resultsmentioning
confidence: 99%
“…For the porcine tissue and prostate experiments, the correction map was computed using a second-order polynomial in Eq. [4]. For the breast imaging experiment, the correction maps were computed using a second-, third-, and fourth-order polynomial fit.…”
Section: Experimental Designmentioning
confidence: 99%
“…12 Previous in vivo canine studies demonstrated the capability of generating thermal patterns that conform to predetermined target volumes 13e17 with 1 to 2 mm accuracy and precision. 14,15 Comprehensive histological analysis revealed the close relationship between acute 100% cell kill and a critical temperature threshold of 55C (on the order of 1 mm), and the peripheral region of enhancement surrounding the NPV on CE-MRI immediately after treatment (on the order of 3 mm). 14,15,18 Delayed cell kill at 48 hours migrated 1 to 3 mm beyond the acute cell kill volume.…”
mentioning
confidence: 99%
“…Another form is MRI-guided percutaneous interstitial microwave thermoablation in locally recurrent tumor. Chopra et al showed that using MRI thermometry while applying transurethral MRI guided high intensity-focused ultrasound (HIFU) allowed for stable temperature measurements 18 to avoid thermal damage of surrounding tissues during the intervention. T2-weighted imaging/DCE-MRI is a promising method for guiding post-HIFU biopsy towards areas containing residual (benign or malignant) viable prostate tissue and to sensitise the detection of locally recurrent cancer in patients with biochemical recurrence.…”
Section: Tumor Aggressivnessmentioning
confidence: 99%